Analisis Faktor Kegagalan Pengobatan Tuberkulosis Berdasarkan Teori Health Promotion Model - Wijar Prasetyo (UIMA Press, 2020)
Introduction: The number of cases of tuberculosis (tuberculosis) to the surrounding community, especially families, is very high, this will make the high number of new cases and cases of failed treatment that impact the occurrence of Multi Drug Resistance (MDR) Objective : To determine the faktors that influence the failure of tuberculosis treatment based on the theory of Health Promotion Model. Method: The design of this research was descriptive correlation with cross sectional approach with independent variables of perceived behavioral benefits, perceived behavioral barriers, perceptions of trust in his abilities, behavior related to influence, inter-personal influence and situational influence, while the dependent variable is the success of treatment. The population was all TB patients in Agats Puskesmas, Agats District, Kabupaten Asmat with a sample of 34 people. The sample selection used the Consecutive sampling method and statistical test using the ANOVA test. Results: Based on the theory of the Health Promotion Model, the success faktor of TB treatment is due to the perceived behavioral benefits that have been carried out 19 (61.3%). The statistical test results showed that the behavioral benefit faktor α = 0.539, the behavioral inhibition faktor α = 0.866, the ability trust faktor α = 0.0463, the interpersonal influence faktor α = 0.761, the significance of the success of TB treatment on the behavior faktor is related to the influence of α = 0.001 with coefficient correlation 0, 508 and Situational Effect with α = 0.003 with a correlation coefficient of 0.484. This shows that the influencing faktor are the influence faktor and the situational influence faktor. Conclusion: Activity faktors have a relationship with influence and personal faktors affecting the success of TB treatment, for that we need a structured client education program and a program of living expenses for TB sufferers to support successful treatment